Unchanging dynamics in posttraumatic growth in cancer patients: ways of coping and illness perception - Bayraktar, Seda; Ozkan, Mine (Frontiers in Psychology, 2023)
Introduction This study aims to address the positive changes due to traumatic experiences, such as being diagnosed with cancer and experiencing this disease for a certain period. Within this purpose, socio-demographic and disease-related variables, coping ways and illness perceptions that affect posttraumatic growth in cancer patients were examined. Secondly, the findings of this study, which is one of the first studies on posttraumatic growth in cancer patients in Turkey, were compared with the findings of current studies on the subject. Method Datums were collected by an interview form and three scales (Posttraumatic Growth Scale, Ways of Coping Inventory and Illness Perception Scale-R) to 78 cancer outpatients in Istanbul University Oncology Institute in 2007. Results Results showed that cancer patients have higher posttraumatic growth levels than the mean. According to analysis, posttraumatic growth total score between confrontive coping (t = −2.344, p < 0.05), self-controlling (t = −3.704, p < 0.001), accepting responsibility (t = −3.032, p < 0.01), escape-avoidance (t = −2.285, p < 0.05), planful problem solving (t = −2.502, p < 0.05), positive reappraisal (t = −5.241, p < 0.001), and seeking social support (t = −3.527, p < 0.01) has relationship. Also, there is a relation between posttraumatic growth subscales and the Revised form of Illness Perception Questionnaire; Change in relationships with others subscale (t = 2.887, p < 0.01) and Change in self-perception subscale (t = 2.660, p < 0.01) between timeline (acute/chronic), Change in self-perception subscale between timeline (cyclical) (t = −2.788, p < 0.01) and uncontrollable body factors (t = −1.916, p < 0.05) Change in philosophy of life subscale between external attributions (t = −2.057, p < 0.05) and Change in relationships with others subscale (t = −2.920, p < 0.01) between chance factors. It was found that positive reappraisal (F = 78.290, p < 0.001), self-controlling (F = 39.814, p < 0.001), and distancing (F = 46.311, p < 0.001) were significant predictors of posttraumatic growth total score. Results showed that ways of coping and illness perceptions were essential variables in posttraumatic growth. Discussion Studies on posttraumatic growth in Turkey and the world have significantly increased in recent years. This study aimed to examine the findings obtained from cancer patients in 2007 in discussion with the findings in the current literature. In this context, it is seen that the relevant variables affecting posttraumatic growth in cancer patients in different cultures do not change.